2022
DOI: 10.3390/antiox11102050
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Alleviates Irradiation Induced Salivary Gland Hypofunction through Preserving Endothelial Cells and Resident Macrophages

Abstract: Radiotherapy for head-and-neck cancers frequently causes long-term hypofunction of salivary glands that severely compromises quality of life and is difficult to treat. Here, we studied effects and mechanisms of Sphingosine-1-phosphate (S1P), a versatile signaling sphingolipid, in preventing irreversible dry mouth caused by radiotherapy. Mouse submandibular glands (SMGs) were irradiated with or without intra-SMG S1P pretreatment. The saliva flow rate was measured following pilocarpine stimulation. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The enrichment of Trpm2 in Csf2r + resident macrophages might be an underlying mechanism for the high radiosensitivity of SMG rMΦs. Another possible mechanism is that IR rapidly damages SMG endothelial cells (Cotrim et al 2007), the major source of multiple factors essential for rMΦ homeostasis, including Cx3cl1 and Dhh reported here and a prosurvival lipid mediator, sphingosine-1-phosphate (S1P) (Yang et al 2022), which in turn contributes to the rapid decrease of SMG rMΦs. These data indicated that irradiation leads to a persistent decrease of salivary gland ILCs and their homeostatic paracrine interactions with Csf2r + resident macrophages, whereas transient Hedgehog activation after irradiation preserves these cells and their interactions.…”
Section: Resultsmentioning
confidence: 96%
“…The enrichment of Trpm2 in Csf2r + resident macrophages might be an underlying mechanism for the high radiosensitivity of SMG rMΦs. Another possible mechanism is that IR rapidly damages SMG endothelial cells (Cotrim et al 2007), the major source of multiple factors essential for rMΦ homeostasis, including Cx3cl1 and Dhh reported here and a prosurvival lipid mediator, sphingosine-1-phosphate (S1P) (Yang et al 2022), which in turn contributes to the rapid decrease of SMG rMΦs. These data indicated that irradiation leads to a persistent decrease of salivary gland ILCs and their homeostatic paracrine interactions with Csf2r + resident macrophages, whereas transient Hedgehog activation after irradiation preserves these cells and their interactions.…”
Section: Resultsmentioning
confidence: 96%
“…When the radiation dose is increased to a certain extent, the expression of SSB1 is not increased but decreased, which may be caused by partial apoptosis and necrosis of cells, weakened repair ability and reduced SSB1 expression due to high dose radiation. The relative expression levels of SSB1 mRNA, SSB1 and NBS1 proteins in rat SMG cells were the highest at 1 h after a single dose of 2Gy irradiation, the dose was lower than those(10 Gy X-rays, HUVECs [61]; 15.0 Gy X rays, SMG-C6 cells [4]) reported in the literatures. Another study with human GBM cell line U87MG as the research object and DNA DSBs as the observation index found that the amount of DSBs in the cells irradiated with 2 Gy of iodine-131 was greater than the cells irradiated with 2 Gy of 6 MV X-ray.…”
Section: Discussionmentioning
confidence: 54%